The use of Terrestrial Laser Scanning for the purposes of preparing technical documentation in BIM technology - Uchański, Łukasz; Karsznia, Krzysztof (Budownictwo i Architektura / Civil and Architectural Engineering, 2018)
Building Information Modelling (BIM) is becoming an increasingly popular solution used both for investment and for reverse engineering aimed at restoring of the original documentation of existing facilities. The reconstruction of an object including its full design properties in an interactive 3D environment makes it possible to carry out structural (including SMH – structural health monitoring) and strength analyses, as well as to provide the effi cient facility management (setting out essential parameters and conducting necessary repairs). This paper aims to assess the laser scanning performed by using an advanced pulse data-capturing device for the development of complex BIM documentation in the Water Centre Laboratory of Warsaw University of Life Sciences – SGGW. Obtained point clouds have been used to build the model for the needs of reverse engineering. Moreover, the authors evaluated the possibility of using a particular type of laser scanner to develop and update complex BIM documentation in the process of facility management.